UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN KELENGKENG (Dimocarpus longan L.) TERHADAP PERTUMBUHAN BAKTERI Streptococcus mutans ATCC 25175 - Selfi Yana; Dianita Febrina Leswara; Pratama Nofran Putra (JOURNAL OF PHARMACEUTICAL (JOP), 2026)
Background: Oral health is a vital aspect of overall well being, however, there are dental caries remains a widespread issue often caused by Streptococcus mutans infection. This bacteria plays a role in plaque formation and enamel demineralization. The use of synthetic antibacterials such as chlorhexidine is quite effective, but has side effects if used long term, so safer natural alternatives are needed. Longan leaves (Dimocarpus longan L.) are known to contain bioactive compounds such as flavonoids, tannins, and phenols which have the potential to be antibacterial. Objective: To determine the antibacterial activity of ethanol extract of longan leaves against the growth of Streptococcus mutans bacteria. Method: This study used the maceration extraction method with 70% ethanol solvent to obtain ethanol extract of longan leaves. The extract was then tested for its secondary metabolite content through phytochemical screening, and was made in three concentrations (20%, 30%, and 40%) to test its antibacterial activity against Streptococcus mutans bacteria using the well diffusion method. Observations were made by measuring the diameter of the inhibition zone, and the data were analyzed to evaluate the antibacterial potential of the extract. Research Results: The results of the phytochemical screening test showed that the ethanol extract of longan leaves positively contained flavonoids, alkaloids, saponins, tannins, and steroids. The average diameter of the inhibition zone against Streptococcus mutans bacteria at concentrations of 20%, 30%, and 40% was 21.1 mm, 22.3 mm, and 23.9 mm, respectively, with a very strong inhibition category and a positive control at a concentration of 0.2% of 20.9 mm with a strong inhibition category. Conclusion: Ethanol extract of longan leaves has antibacterial activity against Streptococcus mutans at concentrations of 20%, 30%, and 40% with increasing inhibition as the concentration increases. The 40% concentration showed the largest inhibition zone compared to 20% and 30%, but did not exceed the positive control of 0.2% chlorehexidine.